Interaction of energy and sulfur microbial diet and smoking status with polygenic variants associated with lipoprotein metabolism - Hur, Haeng Jeon; Yang, Hye Jeong; Kim, Min Jung; Lee, Kyunhee; Jang, Dai Ja; Kim, Myung-Sunny; Park, Sunmin (Frontiers in Nutrition, 2023)
Introduction: Hypo-high-density lipoprotein cholesterolemia (hypo-HDL-C) contributes to the development of cardiovascular diseases. The hypothesis that the polygenic variants associated with hypo-HDL-C interact with lifestyle factors was examined in 58701 middle-aged Korean adults who participated in the Korean Genome and Epidemiology Study (KoGES). Methods:Participants were categorized into the Low-HDL (case; n=16,980) and 721) groups. The participants in the Low-HDL group were selected using the guideline-based cutoffs for hypo-HDL-C (<40 mg/dL for men and <50 mg/dL for women) and included those taking medication for dyslipidemia. The genes associated with hypo-HDL-C were determined through a genome-wide association study (GWAS) in a city hospital-based cohort, and the results were validated in the Ansan/Anung study. The genetic variants for the single nucleotide polymorphism (SNP)-SNP interaction were selected using a generalized multifactor dimensionality reduction analysis, and the polygenic risk score (PRS) generated was evaluated for interaction with lifestyle parameters.The participants with hypo-HDL-C showed a 1.45 and 1.36-fold higher association with myocardial infarction and stroke, respectively. The High-PRS with four SNPs, namely ZPR1_rs3741297, CETP_rs708272, BUD13_rs180327, and ALDH1A2_rs588136, and that with the 11q23.3 haplotype were positively associated with hypo-HDL-C by about 3 times, which was a 2.4-fold higher association than the PRS of 24 SNP with P<5X10 -8 . The risk alleles of CETP_rs708272 and ALDH1A2_rs588136 were linked to increased expression in the heart and decreased in the brain, respectively. The selected SNPs were linked to the reverse cholesterol 4 transport pathway, triglyceride-rich lipoprotein particle remodeling pathway, cholesterol storage, and macrophage-derived foam cell differentiation regulation. The PRS of the 4-SNP model interacted with energy intake and smoking status, while that of the haplotype interacted with a glycemic index of the diet, sulfur microbial diet, and smoking status.Discussion: Adults with a genetic risk for hypo-HDL-C need to modulate their diet and smoking status to reduce their risk.